A Special (Question) View on Wh-Doubling in Lombard Varieties - Jacopo Garzonio; Enrico Castro; Jessica Rita Messina (Languages, 2023)
In this article, we examine a specific type of Wh-Doubling (WhD) that can be observed in some Northern Lombard varieties. Differently from all the previous types of WhD described for Lombard and other Northern Italo-Romance varieties, in the phenomenon we analyze, the two wh-forms are identical and display the -ɛ morpheme. Furthermore, in all the varieties where this type of WhD is present, it is associated with the encoding of special questions and cannot be used in true requests for new information. We propose an analysis of this construction assuming a split-CP representation where the higher wh-form activates a functional projection involved in the expression of special questions. We also hypothesize that this construction derives from an interrogative cleft; if this hypothesis is correct, the formation of the -ɛ morpheme and the re-analysis of the cleft as monoclausal are the two sides of the same process.